The Impact Of Leadership Style, Organizational Systems, And Work Motivation On The Effectiveness Of Madrasah Aliyah In Jambi Province - Kholdun, Ibnu; Risnita; Musli (IJGIE (International Journal of Graduate of Islamic Education), 2025)
This research aims to examine the influence of leadership style, organizational systems, and work motivation on the effectiveness of Madrasah Aliyah Negeri (MAN) in Jambi Province. The study focuses on understanding how leadership, organizational management, and teacher motivation can impact the operational success of Islamic high schools (Madrasah Aliyah) in this region. Using a quantitative approach, the research employs path analysis to assess the relationship between these variables. The results indicate that leadership style, organizational systems, and work motivation each significantly affect the performance and effectiveness of these institutions. The study highlights the importance of a well-structured leadership style and an effective organizational system in fostering an environment conducive to educational success. Additionally, teacher motivation is identified as a key factor influencing both individual and institutional performance. These findings provide valuable insights for educational leaders and policymakers aiming to enhance the quality of education in Madrasah Aliyah institutions